24 hours that changed the world - Hamilton, Adam, 1964- (Abingdon Press, 2009)
No single event in human history has received more attention than the suffering and crucifixion of Jesus of Nazareth. In this book, Adam Hamilton guides us through the last twenty-four hours of Jesus' life. Each chapter is designed to help the reader experience and understand the significance of Jesus' suffering and death.